PERSOALAN PSIKOLOGIS DAN REKONSTRUKSI MITOS DALAM CERITA FANTASTIK PADA KUMPULAN CERPEN BUMI KUNTILANAK KARYA DENNY HERDY - Jatmiko, Dheny; Marsih, Linusia (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
Abstract. Bumi Kuntilanak is collection of short stories written by two young writers: Denny Herdy and Sandza. This article discusses seven short stories by Denny Herdy of the collection, namely "Lunatic", "Samak Lulun", "Memelihara Burung Koreak", "Dunia Setelah Senja", "Kuntilanak", "Dongeng Luna" and "Pelet Marongge". The study found that Denny Herdy’s short stories are fantastic stories that reconstruct the shape of a fairy tale. In addition there are also psychological problems related on human needs structured, namely physiological needs, safety, love and belonging, esteem and self-actualization. This study uses content analysis by utilizing the fantastic theories advanced by Tzvetan Todorov to describe and examine the structure of the fantastic stories. Kata-kata kunci: dongeng, mitos, fantastik, psikologis